MOUNT GĂINA, THE MATRIMONIAL AGENCY OF THE INHABITANTS OF APUSENI MOUNTAINS (PANGEEA, 2025)
The present paper is an essay about Mount Găina, the most important mountain in the Western Carpathians, a true Pantheon of Moți inhabitants. There are many legends, traditions, customs, celebrations, and fairs that were part of the everyday life of its inhabitants.
Keywords: Apuseni Mountains; Mount Găina; Geography; legend